Prognostic and Predictive Potential of CCL5 Expression in Muscle-Invasive Bladder Cancer Patients - Smolka, Cedric; Eckstein, Markus; Jung, Rudolf; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Bahlinger, Veronika; Bertz, Simone; Kehlen, Astrid; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (International Journal of Molecular Sciences, 2024)
Bladder cancer (BC) is the 12th most commonly diagnosed cancer worldwide. Although there are several well-established molecular and immunological classifications, prognostic and predictive markers for tumor cells and immune cells are still needed. Using a tissue microarray, we analyzed the expression of the chemokine CC motif ligand 5 (CCL5) by immunohistochemistry (IHC) in 175 muscle-invasive BC samples. The application of a single cutoff for the staining status of tumor cells (TCs; positive vs. negative) and immune cells (ICs; positive vs. negative) revealed 75 patients (42.9%) and 123 patients (70.3%) with CCL5-positive TCs or ICs, respectively. IHC results were associated with prognostic and predictive data. Multivariate Cox regression analysis revealed that positive CCL5 staining in TCs was associated with significantly shorter disease-specific survival (DSS; RR = 1.51; p = 0.047), but CCL5-negative ICs were associated with significantly shorter overall survival (OS; RR = 1.66; p = 0.005), DSS (RR = 2.02; p = 0.001) and recurrence-free survival (RFS; RR = 1.94; p = 0.002). Adjuvant chemotherapy was favorable for patients with CCL5-negative ICs for OS (RR = 0.30; p = 0.006), DSS (RR = 0.36; p = 0.022) and RFS (RR = 0.41; p = 0.046) but not for patients with CCL5-positive ICs, except in the subgroup of N1 + N2 patients, where it was associated with better OS. We suggest that CCL5 expression can be a prognostic and predictive marker for muscle-invasive bladder cancer patients.
CRIS-Team Scopus Importer:2024-07-12
Keywords: CCL5; chemokine; chemotherapy; immune cells; muscle-invasive bladder cancer; prognosis; tumor cells